Evaluation of biological activity and in silico molecular docking studies of Acanthus ilicifolius leaf extract against four multidrug-resistant bacteria - Kamrun Naher; Md Moniruzzaman; Shirmin Islam; Abdullah Hasan; Gobindo Kumar Paul; Tabassum Jabin; Suvro Biswas; Shahriar Zaman; Md Abu Saleh; Md Salah Uddin (Informatics in Medicine Unlocked, 2022)
Multidrug-resistant bacteria have become a major source of concern around the world, and pharmaceutical waste is a major reservoir of these bacteria. Using morphological, biochemical, and molecular approaches, four bacterial strains were isolated from pharmaceutical waste samples and identified as Staphylococcus aureus, Staphylococcus succinus, Staphylococcus saprophyticus, and Aeromonas jandaei. Through in silico analysis, Acanthus ilicifolius leaf extract was evaluated for identifying lead molecules to inhibit cell division of four multidrug-resistant bacteria. Acanthus ilicifolius had the largest inhibitory zone of 15 mm, 16 mm, 16 mm, and 15 mm against the studied microorganisms at a dose of 150 μg/disc. The DPPH free radical scavenging activity of leaf extract was reported to be 11.89%, 17.50%, and 34.82% at dosages of 50, 100, and 150 μg/ml, respectively, with IC50 values of 246.59 μg/ml, while the IC50 value of BHT was 174.77 μg/ml. These findings showed that the leaf extract had moderately strong antioxidant activity. The brine shrimp mortality was higher at 150 μg/mL dose when compared to others. Molecular docking was used to explore the binding interaction and find lead compounds with a greater affinity for the FtsZ (6YMI) protein, which is responsible for microbial cell division. D1 (CID-31401), D2 (CID-544165), D3 (CID-656583), and D4 (CID-85899374) molecules had binding energies of −8.2 kcal/mol, −8.2 kcal/mol, −7.8 kcal/mol, and −7.8 kcal/mol, respectively. These four compounds found in Acanthus ilicifolius leaf extract could thus be employed to fight antibiotic-resistant bacteria.